2021
DOI: 10.3389/fendo.2020.603432
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Stimulated Thyroglobulin in Reclassifying Low Risk Thyroid Cancer Patients’ Following Thyroidectomy and Radioactive Iodine Ablation: A 7-Year Prospective Trial

Abstract: ContextFollowing total thyroidectomy and radioactive iodine (RAI) ablation, serum thyroglobulin levels should be undetectable to assure that patients are excellent responders and at very low risk of recurrence.ObjectiveTo assess the utility of stimulated (sTg) and non-stimulated (nsTg) thyroglobulin levels in prediction of patients outcomes with differentiated thyroid cancer (DTC) following total thyroidectomy and RAI ablation.MethodA prospective observational study conducted at a University Hospital in Saudi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…22 An observational study in Saudi Arabia reported that 98.0% of DTC patients with a serum Tg concentration below 0.1 ng/ml estimated at 3-6 months post-total thyroidectomy and RAI had no structural or functional disease, which indicates a very low risk of cancer recurrence. 23 This finding was supported by another study that found a significant structural recurrence rate, which was high (30.0%) among DTC patients with a stimulated post-operative thyroglobulin level of more than 2 ng/ml. 24 On the other hand, a retrospective study in 570 DTC patients demonstrated that a low or undetectable postoperative Tg level did not rule out metastases in early stage malignancy; 90.2% of metastatic patients had serum Tg levels below the detection limit.…”
Section: Introductionmentioning
confidence: 53%
“…22 An observational study in Saudi Arabia reported that 98.0% of DTC patients with a serum Tg concentration below 0.1 ng/ml estimated at 3-6 months post-total thyroidectomy and RAI had no structural or functional disease, which indicates a very low risk of cancer recurrence. 23 This finding was supported by another study that found a significant structural recurrence rate, which was high (30.0%) among DTC patients with a stimulated post-operative thyroglobulin level of more than 2 ng/ml. 24 On the other hand, a retrospective study in 570 DTC patients demonstrated that a low or undetectable postoperative Tg level did not rule out metastases in early stage malignancy; 90.2% of metastatic patients had serum Tg levels below the detection limit.…”
Section: Introductionmentioning
confidence: 53%